2011
DOI: 10.1111/j.1447-0756.2010.01437.x
|View full text |Cite
|
Sign up to set email alerts
|

Psychological characteristics of Japanese gynecologic cancer patients after learning the diagnosis according to the hospital anxiety and depression scale

Abstract: Assessment based on the HADS score revealed a high prevalence of psychological problems after announcement of the diagnosis of gynecologic cancer. This emphasizes the importance of psychiatric intervention when patients are informed of their condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
21
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 19 publications
4
21
0
3
Order By: Relevance
“…The prevalence of depression of gynecologic cancer patients has been reported to range from 12 % to 55 %, and major depression has been observed to be much more common in cancer patients than in women with benign disease [19,20]. In our study, the prevalence of depression was 26.4 %.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…The prevalence of depression of gynecologic cancer patients has been reported to range from 12 % to 55 %, and major depression has been observed to be much more common in cancer patients than in women with benign disease [19,20]. In our study, the prevalence of depression was 26.4 %.…”
Section: Discussionmentioning
confidence: 52%
“…Depression affects appetite indirectly, which can aggravate malnutrition. However, the appetite of gynecologic cancer patients has not been documented consistently [20], and thorough active evaluation and assessment are required. Our study results indicate that loss of appetite is associated with malnutrition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We investigated the psychological status of gynecologic cancer patients after diagnosis of cancer with the HADS in 214 gynecologic cancer patients who had been notified that they had cancer at least 2 weeks previously. 11 The cutoff score that indicated the need for patients to have treatment for adjustment disorder was 11 points, and the percentage of patients with a score of 11 points or greater was 55.1% (118/124). The score for anxiety was higher in younger patients, whereas the score for depression was higher in elderly patients.…”
mentioning
confidence: 99%
“…This suggests that the psychological distress of gynecologic cancer patients is not well recognized. 11 Appropriate medical intervention for psychological distress is important to decrease the suffering of patients, improve their QOL, help patients make decisions about treatment, and decrease the burden of caregivers. A meta-analysis has shown that antidepressants are useful for treating major depression in patients with various physical diseases, including cancer.…”
mentioning
confidence: 99%